Najstarsze przedstawienia Piotra Apostoła a problem prymatu papieskiego - Iwaszkiewicz-Wronikowska, Bożena (Vox Patrum, 2004)
The article, which is contained with two parts, treats of the eldest iconography of St. Peter in relation to papal primacy. The author of this article reliances on this iconography and proves that this primacy concerned not only St. Peter but also St. Paul because both of them were founders of Roman Church.